Computer-vision-based technology for fast, accurate and cost effective diagnosis of malaria. (December 2015) - Srivastava, Bina; Anvikar, Anupkumar; Ghosh, Susanta; Mishra, Neelima; Kumar, Navin; Houri-Yafin, Arnon; Pollak, Joseph; Salpeter, Seth; Valecha, Neena
Abstract Background Microscopy has long been considered to be the gold standard for diagnosis of malaria despite the introduction of newer assays. However, it has many challenges like requirement of trained microscopists and logistic issues. A vision based device that can diagnose malaria, provide speciation and estimate parasitaemia was evaluated. Methods The device was evaluated using samples from 431 consented patients, 361 of which were initially screened by RDT and microscopy and later analysed by PCR. It was a prospective, non-randomized, blinded trial. Quantification of parasitaemia was performed by two experienced technicians. Samples were subjected to diagnosis by Sight Dx digital imaging scanning. Results The sensitivity and specificity of the SightDx P1 device for analysed samples were found to be 97.05 and 96.33 %, respectively, when compared to PCR. When compared to microscopy, sensitivity and specificity were found to be 94.4 and 95.6 %, respectively. The device was able to speciate 73.3 % of the PCRPlasmodium falciparum positive samples and 91.4 % of PCRPlasmodium vivax positive samples. Conclusion The ability of the device to detect parasitaemia as compared with microscopy, was within 50 % in 71.3 % of cases and demonstrated a correlation coefficient of 0.89.